O agir linguageiro na perspectiva dos sistemas adaptativos complexos em ambiente virtual de aprendizagem em EAD - Corrêa, Ygor (Universidade do Vale do Rio dos Sinos, 2014)
This study conceives the central role of language in the human development through language acting. In this perspective, it is comprehended that language is situated in interactional practices and it is permanently transformed. This study has an empirical character and a qualitative approach, inserted in the Moodle platform, investigating the specificity of the interactions made in Chats in a Distance Learning Environment according to the Complexity Theory perspective (GLEICK, 1989; JOHNSON 2003; LARSEN-FREEMAN 1997, 2008, 2009; MORIN 2008) and the Sociodiscursive Interactionism perspective (BRONCKART, 1999, 2008). The epistemological comprehension of this study considers that the language acting under development is characterized as a complex adaptive system, in which behaviors eventually emerge from practices of lower level, but not less complex. Then, the interactants develop observing behaviors that emerge from the initial conditions, heading towards self-organization manifestations. The situated language acting on the platform, as well as the situated practices through specific types of discourse (BRONCKART, 2008), are understood as generators of complexity movements. The ways interactants adapted themselves to the discursive context were observed as discursive relations technologically situated. From the analyzed interactions, types of discourse were established and four types of complexity movements, which emerged from the discursive interactions, were proposed: Movement 1 – Discursive Dynamics among interactants; Movement 2 – Non-Interactional linearity; Movement 3 – Agentivity Adaptation (space-time); Movement 4 – Emergent Behavior. The analysis of the situated language acting, through identified types of discourse, presented a low rate of variation in formal language use, as it was expected, due to the formal character of the exchange among pairs. The study allowed us to evidence that the types of discourse are adaptable as the interactants go through phases of interactional change coconstructed in process, alternating between interactive-reporting and mixed theoreticalinteractive types of discourse, by the absence of theoretical discourse.
Keywords: Agir linguageiro; Interações; Sistemas complexos adaptativos; Ambiente virtual de aprendizagem; Educação à Distância; Language acting; Interactions; Complex adaptive systems; Virtual learning environment; Distance learning; ACCNPQ::Lingüística, Letras e Artes::Lingüística